A música representação social em regimes totalitários: varguismo e o canto orfeônico em foco - Parente, Leonel Batista (2015)
This research work is a study about the orpheonics demonstrations occurred in the 1930s, during the totalitarian rule of President Getúlio Vargas (1882-1954). Through ostentatious propaganda, just as Nazism and Fascism, the Vargas policy sought to settle in the collective imaginary of the Brazilian nation the picture of a kind and paternal leader. That context, for spreading the ideology of his government, President Vargas used a series of propaganda mechanisms and one of them was the music, especially in Orpheonic Singing, which includes a range of genres and Brazilian rhythms. In this research, whose objective was to understand the music as power of representation, the theoretical background has focused on Theory of Social Representations, more carefully in the perspective of Roger Chartier, who also meant the Social Representation as a machine to manufacture respect and submission. Based on this theory, to justify the construction of a nationalistic feeling and national identity, this study found the presence of music as a representation of power and submissiveness element in the in the Getúlio Vargas political system.